PENGARUH LINGKUNGAN KERJA DAN MOTIVASI PIMPINAN TERHADAP KINERJA PEGAWAI BKKBN KABUPATEN SUMEDANG - Sri Sukartono Natadiharja (Universitas Tangerang Raya, 2022)
The purpose of this study was to determine the effect of the work environment and leadership motivation on the performance of BKKBN Sumedang employees. The methodology used is descriptive analysis. This method aims to obtain an overview of the symptoms studied in the current state, and on that basis then find answers for problem solving for the existing symptoms. The results of the research analysis can be interpreted that the work environment variable is in the